2022
DOI: 10.3389/fmolb.2022.931759
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in ocular applications and their potential toxicity

Abstract: Nanotechnology has been developed rapidly in recent decades and widely applied in ocular disease therapy. Nano-drug delivery systems overcome the bottlenecks of current ophthalmic drug delivery and are characterized with strong biocompatibility, stability, efficiency, sustainability, controllability, and few side effects. Nanoparticles have been identified as a promising and generally safe ophthalmic drug-delivery system based on the toxicity assessment in animals. Previous studies have found that common nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 194 publications
0
8
0
Order By: Relevance
“…Moreover, while suprachoroidal drug delivery holds promise, it encounters difficulties in effectively transducing the retina post-administration, underscoring the necessity for further research to optimize this approach [ 50 ]. Evaluating the potential toxicity of nanoparticles in ocular applications is indispensable for ensuring their safety and efficacy, accentuating the significance of comprehensive toxicity assessments to address any safety concerns [ 51 ]. By prioritizing efforts to enhance drug contact time, surmount transport barriers, optimize delivery methods such as suprachoroidal administration, and ensure nanoparticle safety, researchers can effectively tackle technical and clinical hurdles in nanoparticle-mediated ocular drug delivery, thereby paving the path for improved treatments and outcomes in ophthalmic care.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, while suprachoroidal drug delivery holds promise, it encounters difficulties in effectively transducing the retina post-administration, underscoring the necessity for further research to optimize this approach [ 50 ]. Evaluating the potential toxicity of nanoparticles in ocular applications is indispensable for ensuring their safety and efficacy, accentuating the significance of comprehensive toxicity assessments to address any safety concerns [ 51 ]. By prioritizing efforts to enhance drug contact time, surmount transport barriers, optimize delivery methods such as suprachoroidal administration, and ensure nanoparticle safety, researchers can effectively tackle technical and clinical hurdles in nanoparticle-mediated ocular drug delivery, thereby paving the path for improved treatments and outcomes in ophthalmic care.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, DNA damage and other stresses can trigger a highly conserved, anticancer, antiaging survival response that inhibits metabolism and growth, enhances defenses, and maintains cellular integrity 275 . A growing number of studies have shown that NP exposure causes DNA damage across cellular barriers 276–278 . For example, TiO 2 ‐NPs have only mild cytotoxic potential, but they can induce ROS and oxidative stress, leading to oxidative DNA damage 279 .…”
Section: Toxicological Mechanisms Of Npsmentioning
confidence: 99%
“…The reduced size and lack of aggregation in dispersed nanoparticles increase their carrying efficiency, enabling them to transport a greater number of drugs to the target tissue [ 28 ]. Additionally, their mucoadhesive characteristic, enhanced permeability, and retention effect allow nanoparticles to accumulate in the target tissue, making them highly attractive for commercial ocular applications [ 29 , 30 ].…”
Section: Overview Of Polymeric Nano-based Drug-delivery System (Dds)mentioning
confidence: 99%